Carnal Knowledge: Towards a 'New Materialism' Through the Arts - Bolt, Barbara; Bolt, Barbara (London Tauris, 2013)
Carnal Knowledge is an outcome of the renewed energy and interest in moving beyond the discursive construction of reality to understand the relationship between what is conceived of as reality and materiality, described as the "material turn." It draws together established and emerging writers, whose research spans dance, music, film, fashion, design, photography, literature, painting and stereo-immersive VR, to demonstrate how art allows us to map the complex relations between nature and culture, between the body, language and knowledge. These writings are unique in the field because they represent the authors' commitment to a new materialism through the creative arts. The questions they address include: Does the material turn in the creative arts take a different turn from continental epistemology, philosophy and the humanities? How does the agency of matter, the material nature of artistic practice and the notion of "truth to materials" affect what we understand as the "new materialism?" In engaging with these questions the book offers perspectives on the emergence of this exciting fresh field of new materialism.